The evaluation of adverse drug reactions in Saudi Arabia: A retrospective observational study - Khalidah A. Alenzi; Najah S. Alanazi; Mohammed Almalki; Homoud alomrani; Fahad O. Alatawi (Elsevier, 2022)
Purpose: This study aimed to assess the type, severity, seriousness, reasons, and outcomes of adverse drug reactions (ADRs) in the reports submitted to the regional spontaneous ADR database. Methods: A retrospective observational study was conducted to analyze all the Tabuk Health Affairs hospitals in Saudi Arabia submitted to SFDA from January 2020 to December 2020. The database was structured according to the Saudi ADR form's fields. The Naranjo algorithm was used to assess the causes of the ADRs (sFDA, 2022). Results: For 1 year, 2,349 ADR reports, along with 242 suspected drugs for 4,114 reactions, were submitted to SFDA. We found more males than females had ADRs (56.1% vs. 43.8%, P < 0.05).Antimicrobial drugs (26.9%), hematologic drugs (19.7%), and neuropsychiatric drugs (12.9%) were responsible for most ADRs. Most of the reactions were associated with the use of ciprofloxacin (7.7%), followed by the combination of lopinavir and ritonavir (4.1%). Two deaths resulted from salbutamol and cefazolin use. Based on the results of the Naranjo assessment of causality, cardiovascular events (9.9%) exhibited the highest score (≥9) for a causal relationship with the suspected drugs, followed by dermatological events (9.5%). Conclusions: The spontaneous report database is an important and valuable source of aftermarket authorization safety information. In our study, most drugs used as antimicrobial, cardiovascular, and hematologic therapies were associated with a higher risk of developing severe and serious events. We recommend monitoring and using medications optimally to ensure patient safety.